Difference in petrophysical properties between foliated and dilatant fault rocks in deeply buried clastics: The case of the Grès d'Annot Formation, SW French Alps. (11th April 2014) - Cavailhes, Thibault; Labaume, Pierre; Sizun, Jean‐Pierre; Soliva, Roger; Gout, Claude; Potdevin, Jean‐Luc; Buatier, Martine; Gay, Aurélien; Chauvet, Alain; Charpentier, Delphine; Travé, Anna
Abstract This study describes normal fault zones formed in foreland arkosic turbidites (the Grès d'Annot Formation, SW French Alps) under deep diagenesis conditions ( 200 °C) and highlights the occurrence of two markedly different fault‐rock types: (1) the foliated fault rocks of the Moutière‐Restefond area; and (2) the dilatant fault rocks of the Estrop area. The deformation of (1) is dominated by intra‐ and transgranular fracturing, pressure solution of quartz and feldspar grains and syn‐kinematic phyllosilicate precipitation resulting from feldspar alteration. The combination of these mechanisms results in a strongly anisotropic strain with intense shortening normal to the foliation (pressure solution) and extension parallel to the foliation (quartz‐ and calcite‐sealed extension veins). This deformation implies local mass transfer that may be achieved without (or with limited) volume change. The deformation of (2) is expressed as dilatant quartz‐sealed veins and breccia textures in which the main mechanisms are transgranular fracturing and quartz precipitation. Type (2) implies fault volume increase, isotropy of deformation and mass transfer at distances larger than in type (1). This study discusses the origins of (1) and (2) and shows that the permeability of (1) is anisotropic, with higher values than the host rocks parallel to the Y main deformation axis (i.e. perpendicular to the slip vector), whereas the permeability of (2) is isotropic and equivalent to that of the host rocks.